Characterization of biol filtration fractionation and photoinactivation kinetics of enterobacteria in the liquid phase - Bellatin Foronda, Israel Sebastiane (2022)
Biogas is one of the best alternatives to produce renewable energy, it uses the waste from agribusiness as the main substrate for its formation. However, when producing significant amounts of biogas, large amounts of biol are generated; solar radiation and environmental oxygen are used to disinfect this compound. To guarantee the desired disinfection, it is necessary to know the kinetics of the death of Enterobacteriaceae by solar radiation and atmospheric oxygen. The objective of this scientific article was to model the disinfection kinetics of the biol, calculating the incidence of accumulated radiation per m ^ 3 of biol, obtained as a by-product of biogas formation, from pig slurry and 1:10 water. Through an analysis of variance (ANOVA) and a multiple comparison test of the treatments using the Tukey test, the synergistic effect of solar radiation and atmospheric oxygen for the solar inactivation of enterobacteria was determined. It was found that to achieve optimal solar disinfection in the biol, its turbidity must be reduced, separating the liquid phase and diluting it with water 1:3. The separation of the phases carried out in the present study reached a volume of 56 per cent with respect to the total volume, retaining 36 and 49 per cent of nitrogen and phosphorus, respectively, of the total volume. With the liquid phase of the biol, a turbidity level (NTU) of 365 was obtained. From this, it was concluded that the atmospheric conditions were appropriate to reduce the load of enterobacteria, reaching the detection limit after 10 hours, with a cumulative radiation of 209.8 watts per m3 of biol. The biocidal effect started from 40 watts per m3 of accumulated radiation biol.